Rancang Bangun Sistem Informasi Inventaris Pada CV.Alan Bakery - Syahril, Syahril; Ibrahim Al Razzak; Irfan Sulthoni; Maurizka Khoirunisa; Desti Syavira Amanda (UNIVERSITAS STEKOM, 2024)
The Inventory Information System designed for CV Alan Bakery is a solution to the challenges of managing raw materials and bread that was previously done manually. CV Alan Bakery is engaged in bread production and sales shop, which requires efficient and accurate stock management. The system is designed using the Unified Modeling Language (UML) as a modeling tool, and implemented using the PHP programming language with the Laravel framework, as well as MySQL as a database management system. The UML approach was used to visually design the system structure, facilitating a better understanding of the relationships between entities in the system. The Laravel framework was chosen to speed up development, ensure security, and improve application performance. MySQL is used as a database to store raw material data, bread, sales transactions, and inventory-related information. This Inventory Information System helps CV Alan Bakery in automating the process of managing raw material and bread stocks. With this, problems related to discrepancies in the calculation of raw materials and bread can be minimized. In addition, the system allows for real-time stock monitoring, sales transaction tracking, and analysis related to inventory performance..